Development of wideband phased array antenna - Mohemed Abdi, Abdinasir (2018)
Wideband communication system covering the range from 4 to 8 GHz requires compact antenna to provide desirable characteristic over whole operating band. This project consists of two designs; first design is presented with optimum geometry of an ultra wideband circular patch antenna. To achieve an UWB characteristic, a patch antenna is designed before proceeding to the bandwidth optimization techniques for the proposed antenna which generates (3.1 – 10.6 GHz). While the second design wideband phased array antenna was realized by adding one element and meander line T-divider, partial ground plane and two slots at ground plane. The antenna was designed and optimized using CST Microwave studio (CSTMWS). The proposed antenna‟s parameters were optimized with various options such as differing the ground plane length, different slot position, and the distance between the elements, and found to operate satisfactorily. An optimized bandwidth has been noticed in this design. Moreover, the antennas structure offers great advantages due to its simple designs and small dimensions working with c-band application. The antenna has been fabricated using FR-4 substrate and tested using network analyzer which has range between 3GHz to 9GHz at the radio frequency (RF) laboratory. Simulation result for wideband 4-8 GHz while the measurement result drops at 7.8 - 4.2 GHz, and the gain is 3.65 dB, and directivity 5.35 dBi. As well as the phase difference between the port 1 to port 2 is -154° and the phase from port 1 to port 3 is 66.8°.The antenna performance showed good agreement between both simulation and measurement results with only some small deviation and this observed deviation is due to the different numerical modeling and meshing techniques.